Age and Parity as Risk Factors for Childbirth Complications: A Systematic Review - Erdira Natasya Putri; Cut Warnaini (Jurnal Biologi Tropis, 2023)
Maternal deaths result from complications during, after pregnancy and childbirth. Factors affecting maternal mortality in Indonesia are 4 too and 3 too late. The main causes that account for nearly 75% of all maternal deaths are postpartum hemorrhage, infection, high blood pressure during pregnancy, complications from childbirth and unsafe abortion. This study aimed to analyze, synthesize, summarize and compare the results of one study with another on "The Relationship of Age and Parity to the Incidence of Complications of Childbirth. The method used in this study was to search various online data centers namely PubMed, Science Direct, Directory of Open Access Journals, Wiley, Cochrane Library, Google Scholar, Scopus. It was found that advanced maternal age and parity status was associated with an increased risk of delivery or obstetrics complication.